A controlled trial of the SibworkS group program for siblings of children with special needs. (August 2015) - Roberts, Rachel M.; Ejova, Anastasia; Giallo, Rebecca; Strohm, Kate; Lillie, Meredith; Fuss, Belinda
Highlights: Siblings of children with a disability are an at risk group for emotional and behavioral problems. We report a controlled trial of SibworkS, a group-based intervention for children who have siblings with special needs. Participation in SibworkS was associated with fewer emotional and behavioral difficulties for siblings immediately post-intervention and at 3 months. Abstract: Siblings of children with a disability are an at risk group for emotional and behavioral problems. This study evaluated an intervention to promote the emotional and behavioral functioning of siblings of children with disabilities and chronic health conditions. SibworkS is a six-week manual-based, cognitive–behavioral group support program focussed on strengthening siblings' perceived social support, self-esteem, problem-solving skills, adaptive coping behaviors and positive sibling relationships. Fifty-six children aged 7–12 were allocated to either the SibworkS program ( n  = 30) or waitlist control ( n  = 26) in alternating sequence. The primary outcome was siblings' emotional and behavioral functioning. Additional outcomes were self-esteem, perceived social support, the sibling relationship and coping behaviors. Siblings were followed-up immediately after the intervention and at 3-months. Siblings participating in the SibworkS intervention were reported to have fewer emotional and behavioral difficulties than siblings in the control group immediately following the intervention and at the 3-month follow-up. Participation in SibworkS was associated with fewer emotional and behavioral difficulties for siblings. Implications for practice and future research include recommendations for improving program participation.